BASLAWÍSH KLASSLARDA ANA TILI SABAQLARÍNDA TEXNIKALÍQ HÁM KÓRGIZBE QURALLARDAN PAYDALANÍWDÍŃ MAZMUNÍ - Annayeva, M.R. (ILIM hám JÁMIYET, 2023)
The article notes the importance of visual aids in the process of teaching the native language in primary scool. The role and function of technical tools in working with texts has been revealed.